Return of minors and European public order: the Bosphorus doctrine of equivalent protection - Ballesteros Barros, Ángel María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This study analyses whether the fundamental rights affected by child abduction’s cases enjoy of equivalent protection in the European Union and in the European human rights system, examining the validity of the Bosphorus doctrine. The author questions whether, in matters of the return of minors in the European Union, the construction of a European public order could be affirmed, with a different content of the international public order of the States and equivalent to the public order in the European Union.